Social entrepreneurship, complex thinking, and entrepreneurial self-efficacy: Correlational study in a sample of mexican students - José Carlos Vázquez Parra; Patricia Esther Alonso-Galicia; Marco Cruz-Sandoval; Paloma Suárez-Brito; Martina Carlos-Arroyo (Administrative Sciences, 2023)
This article presents the results of a study conducted on a sample population of students attending a technological university in western Mexico. The development of the entrepreneurial self-efficacy competency was evaluated within a process of ideation of social entrepreneurship projects to develop social entrepreneurship and complex thinking competencies. A multivariate descriptive analysis was implemented to demonstrate possible statistically significant correlations between the competencies of social entrepreneurship, complex thinking, and entrepreneurial self-efficacy. The results confirm the correlations between the competencies of social entrepreneurship, complex thinking, and entrepreneurial self-efficacy, concluding that there is statistically significant information to indicate that the complex thinking competency positively impacts not only the process of generating social entrepreneurship projects but also the scaling of entrepreneurs' perceptions about their capabilities at the time of entrepreneurship. At a practical level, this study presents results that argue for the need to develop complex thinking in students in social entrepreneurship programs, both in universities and in organizations that promote entrepreneurship. It confirms that complex thinking is a valuable competency in the ideation and generation of entrepreneurial proposals.
Keywords: 350; complex thinking; educational innovation; future of education; higher education; professional education